ANALISIS EFISIENSI PADA USAHATANI JAGUNG DI KAWASAN AGROPOLITAN KABUPATEN CIAMIS - Lidya Nur Amalia; Candra Nuraini; Ade Komaludin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Corn is one of the food crop commodities cultivated in Ciamis Regency, one of which is in the Ciamis Regency agropolitan area. The differences of corn farming productivity at five locations in the agropolitan area which shows the use of production factors is not yet efficient. The research was carried out using a survey method on corn farmers in Panumbangan District which was taken as the research location intentionally (purposive sampling). The population size is 1,545 people and the samples are 94 people is determined using the Slovin formula. Analysis of technical efficiency were analyzed using a stochastic frontier production function, allocative efficiency were analyzed using a cost function where the data analysis used the Front4.1 application. Economics efficiency is combination between technical efficiency and allocative efficiency. The results showed the level of efficiency achieved in corn farming in the agropolitan area of Ciamis Regency were efficient (>0.70), with an average of 0.88 for technical efficiency; an average of 0.81 for allocative efficiency; and an average of 0.72 for economics efficiency